Flood Mitigation Strategies in Rajabasa Subdistrict, Bandar Lampung and Analysis of On-Site Flood Conditions - Dewi, Helen Selvia; Hesti, Hesti; Mulyasari, Rahmi; Haerudin, Nandi; Karyanto, Karyanto (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2025)
Flood disasters frequently occur in Rajabasa Village, Bandar Lampung, particularly during periods of intense rainfall. This study seeks to examine the primary causes of flooding and assess mitigation strategies that can be implemented using spatial planning and community engagement approaches. The research methods include spatial analysis, interviews with local residents, and hydrological modeling through HEC-RAS software. Findings reveal that the main causes of flooding are inadequate drainage infrastructure, land use change, and waste-induced waterway blockages. Therefore, enhancing drainage capacity, promoting riverbank vegetation, and fostering public awareness on environmental cleanliness are essential mitigation efforts.